STRATEGI PERGESERAN DOMINASI OJEK ONLINE LOKAL TERHADAP OJEK ONLINE NASIONAL - Farhan Farhan; Saifuddin Saifuddin; Abidin Nurdin (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
Domino Island Online Gambling Game is a fee-based game and local online motorcycle taxis are transportation that compete with national online motorcycle taxis such as Grab and Gojek. Local online motorbike taxis are able to dominate the Banda Aceh area by carrying out various strategies so that they can become the number one local online motorcycle taxi in Aceh Province in particular. This research examines the strategy of shifting the dominance of local online motorcycle taxis to national online motorcycle taxis. With a focus on the causes of the domination of local online motorcycle taxis to national online motorcycle taxis and the forms of service provided by local online motorcycle taxi drivers to national online motorcycle taxi drivers. This study uses Michael Faucalt's Power Relations Theory. The results of this study indicate that the domination of local online motorcycle taxis over national online motorcycle taxis is the strategy of distributing brochures, cooperation with MSMEs, Social Media and print media and utilizing community relations in order to become an advanced local online motorcycle taxi. While the form of service provided is safety and comfort as well as lots of discounts given by local online motorcycle taxisGame Judi Online Domino Island merupakan game yang berbasis bayaran dan Ojek online lokal merupakan transportasi yang bersaing dengan ojek online nasional seperti Grab dan Gojek. Ojek online lokal mampu menguasai wilayah Banda Aceh dengan melakukan berbagai strategi agar bisa menjadi ojek online lokal nomor satu di Provinsi Aceh khususnya. Penelitian ini mengkaji strategi pergeseran dominasi ojek online lokal terhadap ojek online Nasional. Dengan fokus penyebab terjadinya dominasi ojek online lokal terhadap ojek online Nasional dan bentuk pelayanan yang di berikan ojek online lokal terhadap ojek online Nasional. Penelitian ini menggunakan Teori Relasi kuasa Michael Faucalt. Hasil penelitian ini menunjukkan bahwa terjadinya dominasi ojek online lokal terhadap ojek online Nasional adalah adanya strategi penyebaran brosur, kerja sama UMKM, Media Sosual dan media cetak serta memanfaatkan relasi komunitas guna bisa menjadi ojek online lokal yang maju. Sedangkan bentuk pelayanan yang diberikan adalah keamanan dan kenyamanan serta banyak diskon yag diberikan ojek online lokal